(1184) Open Unemployment in the Egyptian Economy - Amr Mohei- El Din (معهد التخطيط القومى, 2026)
abs This study challenges the prevailing theoretical assumption in development economics that unemployment in developing countries is essentially disguised or underemployment rather than open unemployment in the conventional sense, arguing that Egypt faces a real and growing problem of open unemployment involving individuals actively seeking wage employment and unable to satisfy their demand for work. The author systematically critiques the available measurement sources — population censuses conducted at intervals of ten to twelve years, non-compulsory labor office registration, and labor force sample surveys — demonstrating that the general unemployment rate averaged around 4.6% between 1957 and 1961, while urban rates consistently exceeded this average, surpassing 10% in the five major governorates of Cairo, Alexandria, Port Said, Suez, and Ismailia, with Cairo and Alexandria together accounting for over half of total open unemployment. The study examines several structural dimensions: the sectoral pattern of unemployment revealing particular severity in industry and among new labor market entrants; educated unemployment as a form of misallocated human capital investment arising from the persistent divorce between educational planning and economic planning; and urban unemployment as a phenomenon intensified by rural-to-urban migration flows that far outpaced the growth of employment opportunities in manufacturing and services — with migrant labor comprising 40 to 55% of the urban labor force between 1937 and 1966. The analysis draws on national statistics and labor force surveys to construct a nuanced picture of open unemployment's urban concentration and demographic structure, providing a rigorous empirical foundation for labor market policy in mid-1970s Egypt. تُعالج هذه الدراسة إشكاليةً نظرية وتطبيقية بالغة الأهمية، إذ تنطلق من نقد الاعتقاد السائد في أدبيات التنمية الاقتصادية القائل بأن البطالة في الدول النامية هي في جوهرها بطالة مقنّعة أو بطالة ناقصة لا بطالة سافرة مكشوفة؛ ويُبرهن المؤلف على أن مصر تعاني من مشكلة حقيقية ومتزايدة من البطالة السافرة بمفهومها الكلاسيكي، أي وجود أفراد يطرحون أنفسهم في سوق العمل وهم عاجزون عن إيجاد فرص عمل. ويُقدّم المؤلف نقداً منهجياً لمصادر قياس البطالة في مصر، مُستعرضاً قصور التعدادات السكانية التي تُجرى على فترات طويلة تتراوح بين عشر واثنتي عشرة سنة، وعدم إلزامية تسجيل العاطلين في مكاتب القوى العاملة، مستنداً في جوهر تحليله إلى بيانات مسح القوى العاملة. وتكشف الأرقام أن معدل البطالة العام تراوح بين 4.6% في الفترة 1957-1961، غير أنه في المناطق الحضرية الكبرى كالقاهرة والإسكندرية والسويس وبورسعيد والإسماعيلية تجاوز 10%، وأن القاهرة والإسكندرية وحدهما يستأثران بأكثر من 50% من إجمالي حجم البطالة السافرة. ويتناول المؤلف بالتحليل المحاور الكبرى للبطالة السافرة متضمنةً: طبيعة سوق العمل الحضري وضغوط الهجرة الداخلية الوافدة من الريف المكتظ، والبطالة قطاعية الطابع لا سيما في الصناعة والخدمات، والبطالة بين المتعلمين التي تمثل هدراً في الاستثمار البشري نتيجة الفصل بين التخطيط التعليمي وتخطيط القوى العاملة، فضلاً عن البطالة الحضرية بوصفها ظاهرة تتفاقم مع التحضر ومحدودية الطاقة الاستيعابية للتوظيف في الأنشطة التحويلية والخدمية. وتُسهم الدراسة إسهاماً أصيلاً في استيعاب أبعاد قضية العمالة في مصر إبان سبعينيات القرن الماضي وتوجيه السياسات العامة نحو مواجهتها.